(untitled) (Comprehensive Journal of Science, 2025)
This study examines a seawater desalination plant using the Multi-Stage Flash (MSF) method. The MSF desalination process relies on a thermal system that uses waste heat or an external heat source to evaporate seawater, making it one of the most commonly used desalination methods in the Arabian Gulf region, which suffers from water scarcity. This type of desalination plant is characterized by high production capacity, especially when operated alongside power plants. The system consists of several stages of flashing, where seawater is evaporated and condensed to extract fresh water. • The study focuses on the technical aspects of the plant, its development, and efficiency in terms of productivity and energy consumption, as well as comparisons with other technologies such as reverse osmosis. The study highlights the importance of concentrating on improving the thermal performance of MSF plants by reducing heat loss and improving energy recovery systems. It also addresses the challenges posed by scale formation and corrosion, proposing appropriate chemical treatments to minimize these issues. The study concludes with recommendations to improve MSF plant performance and maintain environmental sustainability.